Anger and creative process engagement in the organisational context - Costa, Carla Filipa Gomes da (2017)
The study of affect related to creativity has been relied on the valence-based approach, considering differences between positive and negative emotions. The valence dimension has been the distinct factor among each group of emotions, instead of analysing discrete emotions with particular characteristics and how they affect creativity (Baas, De Dreu & Nijtad, 2008; George & Zhou, 2002). The goal of this dissertation is to consider the specificity of one discrete emotion – anger – based on the specific emotion approach, which asserts that each emotion has its idiosyncrasies (Lerner & Keltner, 2000; Zeelenberg & Pieters, 2004). It was studied anger relationship with creative process, which is the process leading to creative outcomes and that has been less studied than creative outcomes (Shalley & Gibson, 2004). This relationship included the interaction effects of some relevant moderators. The first article studies individual characteristics influencing creative process engagement, such as state anger and trait anger temperament. Emotion regulation as a moderator of these relationships was considered, as an emotional skill influenced by social norms. The second article discusses the existing differences in the relationship between anger and the three levels of creative process engagement. It is also considered the relevance of contextual factors in this relationship by analysing the moderation role of co-worker support and relationship conflict. The third article attempts to study how anger is caused by emotional exhaustion and competitive psychological climate. The main contributions are discussed from a human resources development and management perspective.